Sunflower Seed Cake and Larvae MassRheological Properties Analysis During Pressing WithVarying Temperature, Pressure and Oil Content - Shorstkii, Ivan; Gukasyan, Alexandr; Koshevoi, Evgeny; Kosachev, Vyacheslav (KnE Life Sciences, 2022)
For the successful implementation of alternative protein sourcesforbiorefinery, optimization of the process parameters is crucial. Knowledge of the rheological propertiesis necessary for the design and development of appropriate equipment and process calculations.The objective of this research was to evaluate the effect of the following pre-treatments: temperature, pressure andeffect of initial oil content on the rheological properties of sunflower seedcake and larvae tissue. The rheological behavior of two protein sourceswas determined by using a rotational viscometer with a hydraulic system and thermostatic bath attached to the equipment. Using the mathematical apparatus and experimental data it was observed that the plastic viscosity of the sunflower seed cake corresponded to the viscosity of the vegetable oil, which confirmed the Bingham rheology assumption put forward in this work. For the larvae mass, a Hershey Buckley fluid model was proposed.A positive linear relationship was found for pressure and a negativelinear relationship was found for the oil content of the sunflower seed cake and larvae tissue on shear stress. Keywords: rheological property, sunflower seed cake, larvae, pulsed electricaldischarge, viscoplasticity flow, Bingham model, modelling